Total Synthesis and Stereochemistry Assignment of Nucleoside Antibiotic A‐94964. Issue 14 (16th February 2022) - Shao, Xiaofei; Zheng, Chang; Xu, Peng; Shiraishi, Taro; Kuzuyama, Tomohisa; Molinaro, Antonio; Silipo, Alba; Yu, Biao
Abstract: A collective total synthesis of eight diastereoisomers associated with NMR analysis leads to a full stereochemistry assignment of the structurally unique nucleoside antibiotic A‐94964, which features an octuronic acid uridine core decorated with an α‐D‐mannopyranosyl residue and an α‐D‐ N ‐acylglucosaminopyranosyl residue via a phosphodiester bridge. Abstract : Full stereochemical assignment of the structurally unique nucleoside antibiotic A‐94964, which shows potent inhibitory activity against the vital bacterial phospho‐ N ‐acetylmuramyl‐pentapeptide translocase, was achieved by the collective total synthesis of eight diastereoisomers in combination with NMR analysis.